Infant vitamin D supplementation and allergic conditions in adulthood - Northern Finland Birth Cohort 1966 - Hypponen, E; Sovio, U; Wjst, M; Patel, S; Pekkanen, J; Hartikainen, AL; Jarvelin, MR (NEW YORK ACAD SCIENCES, 2004)
Allergen-induced secretion of Th2-type cytokines and IgE production have recently been reported to be increased in mice treated with 1,25(OH)(2)D, the active form of vitamin D. Our objective was to investigate whether vitamin D supplementation in infancy is associated with the risk of atopy, allergic rhinitis, and asthma. The Northern Finland Birth Cohort 4-onsists of all individuals in the two most northern provinces of Finland who were due to be born in 1966. Data on vitamin D supplementation during the first year of life was obtained in 1967. Current asthma and allergic rhinitis were reported at age 31 years (n = 7,648), and atopy determined by skin-prick test in a sub-sample still living in northern Finland or the Helsinki area (n = 5,007). The prevalence of atopy and allergic rhinitis at age 31 years was higher in Participants who had received vitamin D supplementation regularly during the first year compared to others (OR 1.46, 95% CI 1.4-2.0, and OR 1.66, 95% CI 1.1-1.6, respectively). A similar association was observed for asthma (OR 1.35, 95% CI 0.99-1.8). These associations persisted after adjustment for a wide range of behavioral and social factors (adjusted: OR 133 for all, P = 0.01. for atopy, P = 0.001 for allergic rhinitis, and P = 0.08 for asthma). We observed an association between, vitamin D supplementation in infancy and an increased risk of atopy and allergic rhinitis later in life. Further study is required to determine whether these observations reflect long-term effects on immune regulation or differences in unmeasured determinants of vitamin D supplementation.